Sticking our nose into the Sonorini tribe: A new genus and species of snake (Squamata: Colubridae: Sonorini) from the Balsas Basin of Mexico - Antonio Y. Cisneros-Bernal; Ricardo Palacios-Aguilar; Carlos Hernández-Jiménez; Eric N. Smith; Oscar Flores-Villela; Cristian Hernández-Morales; Oscar Olivares Loyola; Gustavo Campillo-García (PLoS ONE, 2025)
The colubrid snake tribe Sonorini, which is largely composed of semifossorial and fossorial species, has undergone a series of taxonomic changes in the last few decades. New species have been added, multiple genera have been synonymized, and phylogenetic relationships have been tested using molecular systematics. Our field explorations of the dry Balsas Basin within the Mexican state of Puebla recently resulted in the procurement of two specimens of an unknown Sonorini species. Based on an integrative methodology of genetic and morphological data, we conclude that these specimens represent a hitherto unnamed genus and species, which we describe herein. This new genus is closely related to the other monotypic, Mexican endemic genera Pseudoficimia and Sympholis , but is easily diagnosable from them.